Unveiling the Influence of Servant Leadership on Teacher Job Satisfaction : A Study on the Mediating Effects of Work Motivation, Organizational Culture, and Organizational Climate - Sunarni Sunarni; Sultoni Sultoni (Universitas Pendidikan Mandalika (UNDIKMA), 2023)
This study aims to: (1) describe the variable servant leadership, teacher job satisfaction, work motivation, organizational culture, and organizational climate, (2) analyze the relationship between servant leadership and teacher elementary school job satisfaction moderated by work motivation, organizational culture, and organizational climate, and (3) analyze the influence of servant leadership on teacher job satisfaction moderated by work motivation, organizational culture, and organizational climate. The approach used in this research is quantitative, with descriptive and correlation method. The population of the research is elementary school teachers in the Nganjuk Regency, with a total of the sample are 274 respondents. Samples were taken by non-probability sampling, namely purposive sampling. Data were taken by questionnaire. The data analysis technique used SPSS relation 24.0 and SmartPLS 4. The results of the study: (1) The description of servant leadership was dominated by excellent answers, teacher job satisfaction respondents answered satisfied, very high work motivation, good organizational culture, and good organizational climate. (2) The results of the path analysis simultaneously show a relationship. However, partially the relationship between servant leadership and teacher job satisfaction has only a relationship if moderated by the variables of work motivation and organizational climate, which have a significant relationship. In contrast, moderation of organizational culture has nothing to do. (3) there is an influence between servant leadership and teacher job satisfaction which is moderated by work motivation, organizational culture, and organizational climate. The results of the analysis of specific indirect effects are, the strongest is the relationship between servant leadership and teacher job satisfaction which is moderated by organizational climate variables. The results of the analysis of the influence between variables, namely that there is a contribution between servant leadership and teacher job satisfaction which is moderated by work motivation, organizational culture, and organizational climate.